Ugly aesthetic perception associated with emotional changes in experience of art by behavioural variant of frontotemporal dementia patients. (August 2016) - Boutoleau-Bretonnière, Claire; Bretonnière, Cédric; Evrard, Christelle; Rocher, Laetitia; Mazzietti, Audric; Koenig, Olivier; Vercelletto, Martine; Derkinderen, Pascal; Thomas-Antérion, Catherine
Abstract: The aesthetic experience through art is a window into the study of emotions. Patients with behavioural variant of frontotemporal dementia (bvFTD) have early alteration of emotional processing. A new appreciation of art has been reported in some of these patients. We designed a computerized task using 32 abstract paintings that allowed us to investigate the integrity of patients' emotions when viewing the artwork. We evaluated both conscious and explicit appraisal of emotions [aesthetic judgment (beautiful/ugly), emotional relevance (affected or not by the painting), emotional valence (pleasant/unpleasant), emotional reaction (adjective choice) and arousal] and unconscious processing. Fifteen bvFTD patients and 15 healthy controls were included. BvFTD patients reported that they were "little touched" by the paintings. Aesthetic judgment was very different between the two groups: the paintings were considered ugly (negative aesthetic bias) and unpleasant (negative emotional bias) more often by the patients than by controls. Valence and aesthetic judgments correlated in both groups. In addition, there was a positive bias in the implicit task and for explicit emotional responses. Patients frequently chose the word "sad" and rarely expressed themselves with such adjectives as "happy". Our results suggest that bvFTD patients can give an aesthetic judgment, but present abstraction difficulties, as spectators, resulting from impairments in the cognitive processes involved. They also have difficulties in terms of emotional processes with the loss of the ability to feel the emotion per se (i.e., to feel an emotion faced with art) linked to behaviour assessment. This cognitive approach allows us to better understand which spectators are bvFTD patients and to show interactions between emotions and behavioural disorders. Highlights: Many works in neuroaesthetics reflect the interactions between emotion, creativity and aesthetic judgment. BvFTD patients undergo early changes in emotional processing. Abstracts paintings were more often considered ugly and unpleasant by the bv FTD patients than by controls. BvFTD patients have also very different emotional relevance when viewing abstract paintings than controls. The loss of the ability to feel the emotion per se (i.e., to feel an emotion faced with art) is linked to behavioural assessment.